IMPLEMENTASI AKSIOLOGI PADA KEARIFAN LOKAL DALAM UPAYA MENINGKATKAN PENDIDIKAN KARAKTER SISWA - Hijrianti; Al Humairah Tsaniatul Fallah; Elsa Mayora; Deni Priyadi; Ida Sugiastutik; Elda Wati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to identify the local wisdom-based learning model applied at SMAN 5 Mataram. This study uses a qualitative descriptive method, with data collection through interviews, observations, and documentation. The subjects of the study were teachers and students at SMAN 5 Mataram. The results of the study indicate that the local wisdom-based learning model at this school consists of several aspects, namely: (1) Steps in implementing the learning process and methods used by teachers in teaching local wisdom to students, (2) Efforts to develop local wisdom are carried out by linking learning materials with the local wisdom of the Sasak tribe, (3) The usefulness of this local wisdom-based learning is more focused on increasing student awareness of the importance of local culture, and (4) Challenges in implementing this local wisdom-based learning arise from two perspectives, namely from the perspective of students and teachers.